Masahista the masseur - Mendoza, Brillante; Pastor, Boots Agbayani (Viva Video, 2007)
Iliac is a twenty-year-old masseur in a massage parlor that caters to gay clientele. In here, sex is an immediate consequence of massage. One ordinary night, a homosexual romance novel writer becomes Iliac's first customer for the day. But once outside the parlor, his current girlfriend, a bar girl who works in a Japan, asserts her sexual dominion over him. Back home, his estranged father dies and as Iliac makes the trip to the province, he is faced with the reality of death, love, life and survival. The masseur then carries out his defined duties and roles to his father and family, to his girlfriend, to his trade and to the one customer who has made him favorite and seems to return for more.